PERKEMBANGAN PEREKONOMIAN SYARI’AH PADA MASYARAKAT PONOROGO (Analisis Faktor Internal dan Eksternal ) - Yeni Cahyono; Edy Kurniawan (Universitas Muhammadiyah Ponorogo, 2016)
This study aimed to analyze the internal and external factors in Ponorogonese society that affect the economical development of sharia in Ponorogo. Methods of data analysis used in this study were the validity test, reliability test, test of multiple linear regression analysis, t-test and F test. The population in this study were all customers of Islamic banks. Because of the study population was quite a lot, then the data collection sample of 110 respondents used sample random sampling technique. The results of the analysis showed that from multiple linear regression test, the obtained value of Adjusted R Square was 0.554, which meant the independent variables influence a client's decision were about 82.4%, and 17.6% were influenced by the other independent factors beyond the research. The dominant factor influencing the customer's decision to use a product of Islamic banks was the motivation of customers that was 53.9%..